A xylan-assisted rapid detection test paper for organic pollutants and its preparation method and application

By using xylan as a reducing agent and anchoring agent, a rapid detection test strip for solid-loading of gold and silver bimetal nanoparticles was prepared, which solved the problems of low detection sensitivity and poor reusability of SERS substrates, and achieved high sensitivity to organic pollutants and Stable detection.

CN115629055BActive Publication Date: 2025-02-11SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211127288.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-02-11
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

In the prior art, the detection sensitivity of SERS substrates is low, the reusability is poor, and the commonly used reducing agents and dispersants are highly toxic, making them not suitable for the production of food testing test strips.

Method used

Using xylan as a green reducing agent and anchoring agent, gold nanoparticles are prepared by reacting with gold ions, and they are solidly supported on paper substrates, and then reacting with silver ions to form bimetallic nanoparticles to prepare high sensitivity and stability Rapid test strips for organic pollutants.

Benefits of technology

It has achieved rapid, low-cost, real-time and on-site detection of organic pollutants in agricultural products and food, with high detection sensitivity, good stability, strong recycling ability, and comply with the actual national standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115629055B_ABST
    Figure CN115629055B_ABST
Patent Text Reader

Abstract

The present invention discloses a xylan-assisted rapid detection test paper for organic pollutants and its preparation method and application. The preparation method uses xylan as a green reductant and stabilizer to prepare Au-Ag bimetallic doped nanoparticles, and the Au-Ag bimetallic doped nanoparticles are attached to the surface of paper by a paper sheet coating method to prepare a rapid detection test paper for organic pollutants. The detection method of the test paper is based on the principle of Raman enhanced scattering to detect pesticides and other organic pollutants remaining in agricultural products and foods. The xylan-assisted rapid detection test paper for organic pollutants prepared by the present invention has the advantages of convenient operation, high detection sensitivity, strong recycling ability, uniform signal, good stability, and direct in-situ swab detection, and has excellent application value in applications such as rapid detection of pesticide residues, illegal additives, and toxic and harmful substances in agricultural products and foods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of rapid detection of organic pollutants, and specifically relates to a xylan-assisted rapid detection test paper for organic pollutants and a preparation method and application thereof. Background Art

[0002] In the production, processing, storage, packaging, transportation and consumption of agricultural products and foods, rapid and real-time monitoring of pollutants such as pesticides, antibiotics, illegal additives, bacterial pathogens, etc. is of great significance. At present, the commonly used methods for detecting food contaminants include microbial culture, high performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), supercritical fluid extraction (SFE), solid phase microextraction (SPME) and stir bar adsorption extraction (SBSE). Although these analytical methods can meet the requirements of accurate detection, the sample detection process is complicated, costly, time-consuming, and has certain requirements for detection personnel, and cannot meet the requirements of high-throughput rapid real-time screening of on-site samples. The test paper method is a common method for rapid and low-cost detection of organic pollutants such as pesticides, antibiotics, illegal additives, etc. in agricultural products and foods. The detection principles mainly include paper chromatography technology, colloidal gold immunochromatography, colorimetry, enzyme-linked immunosorbent assay, etc. However, these methods have low accuracy and sensitivity and are difficult to quantify.

[0003] Surface enhanced Raman scattering (SERS) technology is considered to be a promising food safety detection technology due to its non-destructive, fingerprint, and high sensitivity. It can be used to detect pesticides, antibiotics, additives, heavy metal pollution, and mycotoxins in agricultural products and food. Traditional SERS active substrates are generally composed of precious metals (such as Au, Ag, Pt, etc.) in the form of rough surfaces, nanoparticle aggregations, or array elements. The dominant enhancement often observed is the electromagnetic enhancement of molecules adsorbed on the metal surface, with an enhancement range of 10 4 -10 12 . It is worth noting that the enhancement of the local electromagnetic field is stronger at the gap between two nanoparticles, which can produce a stronger SERS signal. Therefore, in the preparation process of SERS substrate, it is necessary to use chemical reducing agents, dispersants and stabilizers to prepare and control the size and shape of metal nanoparticles. However, commonly used reducing agents, dispersants and stabilizers are highly toxic, not suitable for the production of food detection test strips, and have harmful effects on the environment. In addition, the loading of metal nanoparticles on the SERS substrate is often not stable enough, easy to aggregate and fall off, resulting in lower activity and poor reusability of the SERS substrate.

[0004] Therefore, how to use natural green polymers as reducing agents, dispersants and stabilizers to prepare metal nanoparticles with uniform shape and size, and as anchoring agents to stably and firmly attach the metal nanoparticles to the SERS substrate, so as to overcome the defects of existing reducing agents, such as high toxicity, low detection sensitivity and poor reusability of SERS substrates, is a technical problem that urgently needs to be solved. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a xylan-assisted rapid detection test paper for organic pollutants.

[0006] The present invention uses xylan as a green reducing agent, gold ions as gold precursors to prepare gold nanoparticles, and uses xylan as an anchoring agent to immobilize gold nanoparticles on the surface of a paper base by coating to prepare a gold nanoparticle immobilized paper base; and then uses silver ions as silver precursors, and after mixing with the gold nanoparticle immobilized paper base, the silver ions are reduced to wrap silver on the surface of the gold nanoparticles, so as to prepare a rapid detection test paper (Au-Ag-FP) of organic pollutants with uniform dispersion and high stability of bimetallic functional nanoparticles. The detection test paper is based on the principle of Raman enhanced scattering (SERS) to rapidly detect organic pollutants, and realizes rapid, low-cost, real-time and on-site detection of organic pollutants such as pesticides, antibiotics, illegal additives, etc. in agricultural products and foods, and fully utilizes the high added value of xylan as agricultural and forestry waste. The xylan-assisted rapid detection test paper for organic pollutants prepared by the present invention has the advantages of simple preparation, convenient operation, uniform signal, high detection sensitivity, good stability, strong recycling ability, and direct in-situ swab detection.

[0007] Another object of the present invention is to provide a xylan-assisted rapid detection test paper for organic pollutants prepared by the above method, wherein the test paper is a gold-silver bimetallic nanoparticle-immobilized test paper (Au-Ag-FP).

[0008] Another object of the present invention is to provide the application of the above-mentioned xylan-assisted rapid detection test paper for organic pollutants in the field of organic pollutant detection.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a xylan-assisted rapid detection test paper for organic pollutants comprises the following steps:

[0011] (1) xylan and / or modified xylan and gold ions are subjected to a reduction reaction with a solvent as a reaction medium to obtain a xylan / gold nanoparticle mixture, and the xylan / gold nanoparticle mixture is coated on a paper surface to obtain a gold nanoparticle-immobilized paper substrate (Au-FP);

[0012] (2) The gold nanoparticle-immobilized paper substrate is immersed in a solution containing silver ions, and the silver ions are reduced by xylan on the Au-FP and / or other auxiliary means to obtain a gold-silver bimetallic nanoparticle-immobilized test paper (Au-Ag-FP).

[0013] Preferably, in step (1), the mass ratio of the xylan and / or modified xylan to the gold ions is 30:1-27.

[0014] Preferably, in step (1), the xylan and / or modified xylan is mixed with the gold ion solution in the form of a solution or dispersion. Before mixing, the concentration of the gold ion solution is 0.1-15 mg / mL, and the concentration of the xylan and / or modified xylan solution or dispersion is 10-100 mg / mL.

[0015] Preferably, the reduction reaction in step (1) is carried out at a temperature of 60 to 100° C. and for a time of 10 to 80 minutes.

[0016] Preferably, in the gold nanoparticle-immobilized paper substrate obtained in step (1), the ratio of the mass of the gold nanoparticles to the area of ​​the paper is 0.5 to 15 g / m 2 More preferably, 1.02 to 5.6 g / m 2 .

[0017] Preferably, the xylan / gold nanoparticle mixture in step (1) is coated on one side or both sides of the paper, with the coating times being 1 to 20 times per side; the coating speed is 50 to 200 mm / s; the coating thickness is 0.1 to 20 μm each time, the time interval between each coating is 5 to 30 min, and the coating drying temperature is 50 to 90°C.

[0018] Preferably, in the solution containing silver ions in step (2), the concentration of the silver ion solution is 0.1 to 10 mg / mL; the solution containing silver ions further contains xylan and / or modified xylan, and the concentration of xylan and / or modified xylan in the system is 0.1 to 25 mg / mL; the solution containing silver ions further contains iron oxide and / or iron oxide hydroxide, and the concentration of iron oxide hydroxide in the system is 1 to 20 mg / mL; the solution containing silver ions further contains sodium borohydride, sodium cyanoborohydride and / or hydroxylamine hydrochloride, and the concentration of iron oxide hydroxide in the system is 1 to 20 mg / mL.

[0019] Preferably, the solution containing silver ions in step (2) is a Tollens reagent, which is obtained by mixing 0.01-2 mol / L AgNO3 solution and 0.5-5 wt% strong alkali aqueous solution in a volume ratio of 1:1-30, and then adding 0.5-5 wt% ammonia aqueous solution until the precipitate just disappears.

[0020] Preferably, the molar ratio of gold in the gold nanoparticle-immobilized paper substrate obtained in step (1) to the molar ratio of silver in step (2) is 1:0.5-10; more preferably 1:4-10.

[0021] Preferably, the immersion time in step (2) is 1 to 5 hours; the other auxiliary reduction methods include at least one of the reduction method of additionally adding xylan as a reducing agent, microwave reaction reduction, chemical reducing agent reduction, and photocatalytic reduction; wherein the power of the microwave reaction of xylan as a reducing agent is 300 to 800 W, the microwave reaction time is 30 to 90 minutes, and the microwave reaction temperature is 60 to 90°C.

[0022] Preferably, the xylan used in the xylan or modified xylan in step (1) is a polysaccharide or modified polysaccharide whose main chain is composed of (1→4)-β-D-pyranose xylan groups extracted from wood fiber raw materials; the wood fiber raw materials are at least one of wood, bagasse, corn cobs, various crop straws, various husks, various fruit shells, peels and seed coats; the modified xylan is at least one of carboxylated modified xylan, acylated modified xylan, esterified modified xylan, etherified modified xylan and quaternized modified xylan, and the degree of substitution of the modified xylan is 0.05 to 1.05.

[0023] Preferably, the paper in step (1) has good water absorption and certain strength, and the paper type is at least one of filter paper, printing paper, wrapping paper, white paper, kraft paper, household paper, and a substrate prepared with synthetic fibers based on paper forming technology.

[0024] The xylan-assisted rapid detection test paper for organic pollutants prepared by the preparation method is a gold-silver bimetallic nanoparticle-immobilized test paper (Au-Ag-FP).

[0025] The application of the xylan-assisted rapid detection test paper for organic pollutants prepared by the above preparation method in the field of organic pollutant detection.

[0026] Preferably, the application is: using xylan-assisted rapid detection test paper for organic pollutants to collect pollutants, and then performing surface enhanced Raman scattering (SERS) detection to analyze and obtain the types and contents of organic pollutants.

[0027] Preferably, the concentration of pollutants collected on the xylan-assisted rapid test paper for organic pollutants is not lower than the minimum detection limit of the test paper; the organic pollutants are at least one of phenols, organophosphorus, aniline, nitrobenzene and organochlorine.

[0028] Preferably, the collecting method is at least one of dipping, wiping after wetting and dripping.

[0029] Preferably, the position of the Raman spectrum enhancement peak obtained by the surface enhanced Raman scattering (SERS) detection is 200-1100 nm.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] 1. The preparation method provided by the present invention can give full play to the structural functionality of xylan itself, and can achieve the reduction, stabilization and anchoring of SERS substrate metal particles in an environmentally friendly manner, without the need to add additional reducing agents and stabilizers to the substrate, thereby causing less interference to the SERS substrate signal.

[0032] 2. The preparation method provided by the present invention improves the disadvantage that rigid solid phase substrates such as silicon wafers, glass or graphite cannot be directly used for in-situ swab detection, and realizes the functionalization of in-situ swab detection and recyclability by using paper coating.

[0033] 3. The SERS test paper based on composite bimetallic nanoparticles prepared by the present invention can further enhance the local electromagnetic field at the gap ("hotspot") between two nanoparticles, generating a stronger SERS signal. Compared with traditional SERS substrate materials, it makes up for the instability of traditional metal materials (it is difficult to ensure the size, morphology, and distribution of metal nanoparticles).

[0034] 4. The preparation method provided by the present invention can effectively utilize xylan resources, overcome the problem of the single existing xylan utilization method, fully tap the high added value of xylan, realize the high-value utilization of xylan as agricultural and forestry waste, and provide a new way for the resource utilization of xylan, which has good economic value and practical value.

[0035] 5. The xylan organic pollutant rapid detection test paper prepared by the present invention has the advantages of being biodegradable, green and environmentally friendly, low cost, simple preparation process, mild preparation conditions, and strong biocompatibility. It is a new technical model that responds to the country's carbon peak and carbon neutrality and conforms to the development of the times.

[0036] 7. The gold-silver bimetallic nanoparticle-loaded test paper (Au-Ag-FP) prepared by the present invention has the advantages of simple preparation, convenient operation, uniform signal, high detection sensitivity, good stability, strong recycling ability and direct in-situ swab detection. The detection of organic pollutants meets or even exceeds the actual national standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a schematic flow chart of a preparation method and a detection method of a xylan-assisted rapid detection test paper for organic pollutants.

[0038] Figure 2These are STEM images of nanoparticles on Au-Ag8-FP obtained in Example 1 at different magnifications.

[0039] Figure 3 Add different concentrations (10 -3 -10 -6 mol / L) Raman spectrum of thiram.

[0040] Figure 4 The Au-Ag-FP test paper obtained by adding 10 -3 mol / L thiram after Raman spectrum.

[0041] Figure 5 The Raman spectrum collection and characteristic peak collection results of Au-Ag8-FP obtained in Example 1, where a is the SERS spectrum collected from 20 points randomly selected from the Au-Ag8-FP substrate (10 -3 mol / L Thiram), b is the 1377cm corresponding to the spectrum in a -1 a is the scatter plot of the intensity of the characteristic peak at the location, c is the SERS spectrum of thiram extracted from the apple surface by the Au-Ag8-FP substrate. It can be observed that the spectrum collection of the test paper at multiple random locations and the distribution of the intensity of the specific characteristic peak can be observed. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0043] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0044] Example 1

[0045] Take 100g bagasse in a Soxhlet extractor and extract it with 95% ethanol for 6h to remove extracts, fats and waxes. After the extraction, the bagasse was dried at 60℃ overnight, and then 4wt% NaClO2 solution was added and bleached for 1h at 75℃, pH=3.9-4.0, and 200rpm. After the reaction was completed, the reaction solution was removed with a filter funnel, and the bagasse was further bleached with 2wt% NaClO2 solution to remove lignin. Finally, the reaction residue was washed with deionized water 3 times, washed with anhydrous ethanol once, and air-dried to obtain holocellulose. Holocellulose was added with 2wt% NaOH solution (solid-liquid ratio 1:20, w:v, unit is g / mL), and reacted at 90℃ and 250rpm for 3h to extract xylan. The filtrate was adjusted to pH 5.5 with acetic acid, and the solution volume was concentrated to one-third of the original volume with a rotary evaporator, and then poured into three times the volume of anhydrous ethanol and allowed to stand overnight. Finally, xylan was obtained by centrifugal separation, washed three times with 70% ethanol, placed in a ventilated place to evaporate the ethanol, and freeze-dried for later use.

[0046] Take xylan (0.15g) and disperse it in 3mL of water to obtain a 5wt% xylan dispersion. Dissolve HAuCl4·3H2O (25mg) in 12mL of water and heat to the reaction temperature. Then add the xylan solution to the above HAuCl4·3H2O solution and react at 60℃ for 80 minutes. When the color changes from yellow to red wine, a xylan / AuNPs particle mixture is obtained. After appropriate dilution, it is measured with a UV-2600i ultraviolet spectrophotometer with a scanning range of 300-800nm.

[0047] Take several 3cm×3cm filter papers, put them in a 105℃ oven for 3h, take them out and cool them to room temperature in a dryer, weigh and record the mass as m1. Use a coating machine to apply the prepared xylan / gold nanoparticle mixture to the surface of the paper, coat each filter paper on both sides, coat each side 10 times, and the coating speed is 100mm / s; after each coating, put it in a 60℃ oven for 15min and then coat it for the second time until the coating number is reached. After coating, put the filter paper in a vacuum drying oven and dry it for 24h, weigh and record the mass as m2, and obtain the gold nanoparticle-supported paper substrate (Au-FP). According to the coating amount, xylan ratio and m2-m1, the loading amount of gold nanoparticles on the paper substrate (the ratio of the mass of gold nanoparticles to the area of ​​paper) is calculated to be 1.37g / m 2 .

[0048] Add 1.2 mL of 2 wt% NaOH aqueous solution to 0.5 mL of 0.1 mol / L AgNO3 solution, and then drip 2 wt% ammonia solution until the precipitate just disappears to obtain Tollens reagent. Add 0.1 mL of 10 mg / mL xylan dispersion to prepare a mixed solution. Then immerse the previously obtained Au-FP in the mixed solution, put it into a microwave reactor, react at 800 W, 65 ° C for 30 minutes, take it out, put it into a vacuum drying oven and dry it for 24 hours to obtain a gold-silver bimetallic nanoparticle-immobilized test paper (Au-Ag-FP), in which the molar ratio of silver to gold in the raw material AgNO3 and the gold nanoparticle-immobilized paper base is 8, so it is named Au-Ag8-FP. In addition, by adjusting the volume of 0.1 mol / L AgNO3 solution added when preparing Tollens reagent, the molar ratios of the raw material AgNO3 and the silver-gold in the gold nanoparticle-immobilized paper were 0.5, 1, 2, 4, and 10, respectively, to obtain the gold-silver bimetallic nanoparticle-immobilized test paper (Au-Ag 0.5 -FP, Au-Ag1-FP, Au-Ag2-FP, Au-Ag4-FP, Au-Ag 10 -FP).

[0049] The structure of gold-silver bimetallic nanoparticles was characterized. STEM dark field images of nanoparticles on Au-Ag8-FP at different magnifications are shown in Figure 2. Figure 2 shown.

[0050] Take 10 -3 , 10 -4 , 10 -5 , 10 -6 mol / L thiram ethanol solution was dripped onto the substrate and placed in a 50°C oven for 5 min. After the ethanol evaporated, the spectrum of the Au-Ag8-FP test paper was collected and characterized under the irradiation of a micro Raman spectrometer with an excitation wavelength of 633 nm to determine the linear relationship between the characteristic peak of the pollutant and the concentration. The test paper was tested by Raman spectroscopy. Figure 3 As shown, the concentration of thiram is 10 -3 mol / L, 1377cm -1 The peak intensity is close to 30000 and the concentration is 10 -4 mol / L, 1377cm -1 The peak intensity is close to 2500 and the concentration is 10 -5 and 10 -6 1377cm at mol / L -1 The peak also has a significant enhancement. -3 mol / L concentration of thiram was added to the Au-Ag bimetallic nanoparticle-immobilized test paper. 0.5-FP, Au-Ag1-FP, Au-Ag2-FP, Au-Ag4-FP, Au-Ag8-FP, Au-Ag 10 -FP and perform Raman spectroscopy detection, the results are as follows Figure 4 As shown in the figure, the test papers with various silver-gold molar ratios all have Raman enhancement phenomenon, among which Au-Ag8-FP has a Raman enhancement at 1377 cm -1 The peak intensity at is close to 30000, Au-Ag4-FP and Au-Ag 10 -FP at 1377cm -1 The peak intensity at is close to 10000.

[0051] At the same time, the reproducibility of Au-Ag8-FP was evaluated by randomly selecting 20 locations on the same substrate and dropping 10 - 3 mol / L thiram solution was used for SERS detection, and the peak intensity reproducibility was excellent ( Figure 5 In addition, in order to test the feasibility of the obtained substrate for in-situ extraction and detection of organic pollution residues on the surface of objects, the surface of apples containing different concentrations of thiram was wiped with a slightly moist Au-Ag8-FP substrate, and then the substrate was irradiated with a Lab RAM Aramis micro-Raman spectrometer to collect SERS spectra. The collected spectra were compared with the characteristic peaks of thiram to evaluate the effect. The distribution of spectrum collection and characteristic peak collection is shown in Figure 5 As shown in c, after the thiram on the substrate was eluted with alcohol and air-dried, the substrate could be reused for detection. After the substrate was repeatedly detected-eluted-detected 20 times, the SERS enhancement performance did not change significantly.

[0052] Example 2

[0053] Take 100g of 20-60 mesh corn stalks in a Soxhlet extractor, and extract the husk particles with a 2:1 volume ratio of benzene-ethanol solution in the Soxhlet extractor for 6 hours to remove the extract, fat and wax. After the extracted corn stalks are dried at 60℃ for one night, 3wt% NaClO2 solution is added, and bleached for 2 hours at 60℃, pH=3.9-4.0, and 300rpm. After the reaction is completed, the reaction solution is removed with a filter funnel, and the corn stalks are further bleached with 2wt% NaClO2 solution to remove lignin. Finally, the reaction residue is washed 3 times with deionized water, washed once with anhydrous ethanol, and air-dried to obtain holocellulose. Holocellulose is added with 6wt% NaOH solution (solid-liquid ratio 1:20, w:v, unit is g / mL), and reacted at 60℃ and 300rpm for 2 hours to extract xylan. The pH of the filtrate was adjusted to 5.5 with acetic acid, and the solution was concentrated to one third of the original volume by a rotary evaporator, and then three times the volume of anhydrous methanol was poured in and allowed to stand overnight. Finally, xylan was obtained by centrifugal separation, washed three times with 70% methanol, and placed in a ventilated place to evaporate the methanol, and vacuum dried for use.

[0054] Take xylan (0.12g) and disperse it in 3mL water to obtain a 4wt% xylan dispersion. Dissolve HAuCl4·3H2O (10mg) in 12mL distilled water and heat to the reaction temperature. Then add the xylan solution to the above HAuCl4·3H2O solution and react at 80℃ for 50 minutes. When the color changes from yellow to red wine, a xylan / AuNPs particle mixture is obtained. After appropriate dilution, it is measured with a UV-2600i ultraviolet spectrophotometer with a scanning range of 300-800nm.

[0055] Take several sheets of 3cm×3cm printing paper, put them in a 105℃ oven for 3h, take them out and cool them to room temperature in a dryer, weigh and record the mass as m1. Use a coater to apply the prepared xylan / gold nanoparticle mixture to the surface of the paper, coat each filter paper on both sides, coat each side 15 times, and coat at a speed of 100mm / s; after each coating, put it in an 80℃ oven for 20min and then coat it a second time until the number of coatings is reached. After coating, put the filter paper in a vacuum drying oven and dry it for 24h, weigh and record the mass as m2, and obtain the gold nanoparticle-loaded paper base (Au-FP). According to the coating amount, xylan ratio, and m2-m1, the loading amount of gold nanoparticles on the paper base (the ratio of the mass of gold nanoparticles to the area of ​​paper) is calculated to be 1.02g / m 2 .

[0056] The Au-FP obtained previously was immersed in 0.4 mL of 0.1 mol / L AgNO3 solution. After immersion for 30 min, 1 mL of 50 mg / mL xylan dispersion was added and reacted for 120 min. Then, the Au-FP was taken out and dried in a vacuum drying oven for 24 h to obtain the gold-silver bimetallic nanoparticle-loaded test paper (Au-Ag-FP).

[0057] Take 10 -3 mol / L phosphine thiophene reagent was dripped on the above substrate, and the spectrum of the SERS sample prepared above was collected and characterized under the irradiation of a micro-Raman spectrometer with an excitation wavelength of 633nm, and the high-performance substrate material was screened out and the linear relationship between the characteristic peak of the pollutant and the concentration was determined. At the same time, in order to evaluate the reproducibility of the same high-performance substrate Au-Ag-FP, phosphine thiophene was randomly selected at 25 locations on the same substrate for SERS detection, and the peak intensity reproducibility was excellent. In addition, in order to test the feasibility of the obtained substrate for in-situ extraction and detection of organic pollution residues on the surface of crops, the surface of oranges containing phosphine thiophene was wiped with a slightly moist Au-Ag-FP substrate, and then the substrate was irradiated with a Lab RAM Aramis micro-Raman spectrometer to collect SERS spectra, and the collected spectrum was compared with the characteristic peak of phosphine thiophene to evaluate the effect. After the phosphine thiophene on the substrate was eluted with alcohol and air-dried, the substrate could be reused for detection. After the substrate was repeatedly detected-eluted-detected 20 times, the enhanced performance of SERS did not change significantly.

[0058] Example 3

[0059] Take 100g of birch wood strips with a diameter of about 5mm and soak them in 300mL acetone solution for 12h, dry them and crush them, and screen out the part with 40-60 mesh sieve holes. Take the above-mentioned appropriate amount of 40-60 mesh birch wood particles, add them to 12wt% KOH solution (solid-liquid ratio 1:12, w:v, unit is g / mL), react at 90℃ and 300rpm for 2h to extract xylan. After the reaction is completed, filter the reaction solution, collect the filtrate, and wash the filter residue with clean water once. At the same time, collect the washing liquid and mix it with the filtrate. After concentrating the solution volume to one-third of the original volume with a rotary evaporator, pour three times the volume of anhydrous propanol and let it stand overnight. Finally, xylan is obtained by centrifugation, washed three times with 70% propanol, and placed in a ventilated place to volatilize the propanol, and freeze-dried for use.

[0060] The obtained xylan was placed in a three-necked flask equipped with an overhung stirrer, and 3 g of maleic anhydride, 0.1 g of N-bromosuccinimide and 80 mL of N,N-dimethylformamide reagent were added. Nitrogen protection was introduced, and the three-necked flask was heated in a water bath at 60°C. After reacting for 6 hours, it was filtered, washed, and dried in an oven at 50°C for 16 hours to obtain carboxylated modified xylan with a degree of substitution of about 0.5.

[0061] Take carboxylated modified xylan (0.3 g) and dissolve it in 3 mL of water to obtain a 10 wt% carboxylated xylan solution. Dissolve HAuCl4·3H2O (50 mg) in 12 mL of distilled water and heat to the reaction temperature. Then add the carboxylated xylan solution to the above HAuCl4·3H2O solution and react at 100°C for 25 minutes. When the color changes from yellow to red wine, a carboxylated xylan / AuNPs particle mixture is obtained. After appropriate dilution, it is measured using a UV-2600i ultraviolet spectrophotometer with a scanning range of 300-800 nm.

[0062] Take several sheets of 3cm×3cm household paper, put them in a 105℃ oven for 3h, take them out and cool them to room temperature in a dryer, weigh and record the mass as m1. Use a coating machine to apply the prepared carboxylated xylan / gold nanoparticle mixture to the surface of the paper, double-sided coating, 5 coating times on each side, and a coating speed of 125mm / s; after each coating, put it in a 70℃ oven for 20min and then apply it a second time until the number of coatings is reached. After coating, put the filter paper in a vacuum drying oven and dry it for 24h, weigh and record the mass as m2, and obtain the gold nanoparticle-loaded paper base (Au-FP). According to the coating amount, xylan ratio, and m2-m1, the loading amount of gold nanoparticles on the paper base (the ratio of the mass of gold nanoparticles to the area of ​​paper) is calculated to be 1.25g / m 2 .

[0063] The Au-FP obtained previously was immersed in 1 mL of 0.05 mol / L AgNO3 solution. After immersion for 60 min, 10 mg of iron oxide and 10 mg of iron hydroxide oxide were added. After complete dissolution, they were irradiated with an ultraviolet lamp with a wavelength greater than or equal to 320 nm for 60 min, taken out, and placed in a vacuum drying oven for 24 h to obtain a gold-silver bimetallic nanoparticle-loaded test paper (Au-Ag-FP).

[0064] Take 10 -5mol / L fungicide thiabendazole was dripped on the substrate, and the spectrum of the SERS sample prepared above was collected and characterized under the irradiation of a micro-Raman spectrometer with an excitation wavelength of 633nm, and the high-performance substrate material was screened out and the linear relationship between the characteristic peak of the pollutant and the concentration was determined. At the same time, in order to evaluate the reproducibility of the same high-performance substrate Au-Ag-FP, 23 places on the same substrate were randomly selected to drip the fungicide thiabendazole for SERS detection, and the peak intensity reproducibility was excellent. In addition, in order to test the feasibility of the obtained substrate for in-situ extraction and detection of organic pollution residues on the surface of crops, a slightly moist Au-Ag-FP substrate was used to wipe the surface of a banana containing thiabendazole, and then the Lab RAM Aramis micro-Raman spectrometer was used to irradiate the substrate to collect SERS spectra, and the collected spectra were compared with the characteristic peaks of thiabendazole to evaluate the effect. After the thiabendazole on the substrate was eluted with alcohol and air-dried, the substrate could be reused for detection. After the substrate was repeatedly detected-eluted-detected 20 times, the enhanced performance of SERS did not change significantly.

[0065] Example 4

[0066] 100g of 20-60 mesh corn stalks were taken into a Soxhlet extractor, and the corn stalk particles were extracted for 6 hours with a benzene-ethanol solution in a volume ratio of 2:1 in the Soxhlet extractor to remove extracts, fats and waxes. The extracted stalks were immersed in a 3wt% sodium chlorite aqueous solution, the pH value was adjusted to 3.8-4.0 with acetic acid, and then heated in a 75°C water bath for 1 hour, and the rotation and shaking were maintained during the heating process. After heating for 1 hour, 3wt% sodium chlorite aqueous solution and glacial acetic acid were added to keep the pH of the system at 3.8-4.0 and immerse the stalks, and continued to heat in a 75°C water bath for 1 hour, and this was repeated 3 times to remove lignin, and then cooled and filtered, the residue was fully rinsed with pure water and then rinsed with 75% ethanol, and then dried in a 60°C oven for 16 hours to obtain holocellulose. The obtained holocellulose was extracted with dimethyl sulfoxide at a solid-liquid ratio of 1:25 (g / mL) and 80°C for 5 hours, cooled and filtered, and the solution volume was concentrated to one-third of the original volume by a rotary evaporator, and then poured into three times the volume of anhydrous ethanol and allowed to stand overnight. Finally, xylan was obtained by centrifugation, washed three times with 70% ethanol, and placed in a ventilated place to evaporate the ethanol, and freeze-dried for use. The xylan extracted by this method is acetylated xylan with a degree of substitution of 0.15.

[0067] Acetylated xylan (0.225 g) was dissolved in 3 mL of water to obtain a 7.5% acetylated xylan solution. HAuCl4·3H2O (180 mg) was dissolved in 12 mL of distilled water and heated to the reaction temperature. The acetylated xylan solution was then added to the above HAuCl4·3H2O solution and reacted at 80°C for 45 minutes. When the color changed from yellow to red wine, an acetylated xylan / AuNPs particle mixture was obtained. After appropriate dilution, it was measured using a UV-2600i ultraviolet spectrophotometer with a scanning range of 300-800 nm.

[0068] Take several 3cm×3cm filter papers, put them in a 105℃ oven for 3h, take them out and cool them to room temperature in a dryer, weigh and record the mass as m1. Use a coating machine to apply the prepared acetylated xylan / gold nanoparticle mixture to the surface of the paper. Each kraft paper is only coated on one side, the number of coatings is 20 times, and the coating speed is 100mm / s; after each coating, put it in an 80℃ oven for 20min and then apply it for the second time until the number of coatings is reached. After the coating is completed, put the filter paper in a vacuum drying oven and dry it for 24h, weigh and record the mass as m2, and obtain the gold nanoparticle-loaded paper substrate (Au-FP). According to the coating amount, xylan ratio and m2-m1, the loading amount of gold nanoparticles on the paper substrate (the ratio of the mass of gold nanoparticles to the area of ​​paper) is calculated to be 5.6g / m 2 .

[0069] The Au-FP obtained previously was immersed in 2 mL of 0.05 mol / L AgNO3 solution. After immersion for 60 min, 10 mg of sodium borohydride was added. After complete dissolution and reaction for 60 min, it was taken out and placed in a vacuum drying oven for 24 h to obtain a gold-silver bimetallic nanoparticle-loaded test paper (Au-Ag-FP).

[0070] Take 10 -6mol / L methyl parathion was dripped on the side of the Au-Ag-FP substrate with gold-silver bimetallic particles, and the spectrum of the SERS sample prepared above was collected and characterized under the irradiation of a micro-Raman spectrometer with an excitation wavelength of 633nm, and the high-performance substrate material was screened out and the linear relationship between the characteristic peak of the pollutant and the concentration was determined. At the same time, in order to evaluate the reproducibility of the same high-performance substrate Au-Ag-FP, methyl parathion was randomly selected at 20 locations on the side of the same substrate with gold-silver bimetallic particles for SERS detection, and the peak intensity reproducibility was excellent. In addition, in order to test the feasibility of the obtained substrate for in-situ extraction and detection of organic pollution residues on the surface of crops, the surface of bananas containing methyl parathion was wiped with the side of the slightly moist Au-Ag-FP substrate with gold-silver bimetallic particles, and then the substrate was irradiated with a Lab RAM Aramis micro-Raman spectrometer to collect SERS spectra, and the collected spectra were compared with the characteristic peaks of methyl parathion to evaluate the effect. After eluting methyl parathion on the substrate with alcohol and air-drying, the substrate can be reused for detection. After the substrate is repeatedly detected-eluted-detected 20 times, the SERS enhancement performance does not change significantly.

[0071] Comparative Example 1

[0072] In this comparative example, the type of hemicellulose was replaced by glucomannan from xylan, and the other parts were the same as Example 1. Since glucomannan does not have a reducing aldehyde group, Au or Ag or Au-Ag nanoparticles cannot be prepared, and the prepared substrate Raman enhancement performance is poor, and thiram cannot be detected.

[0073] Comparative Example 2

[0074] In this comparative example, xylan was replaced with sodium borohydride or hydrazine hydrate as a reducing agent to prepare Au or Ag or Au-Ag nanoparticles, and the other parts were the same as Example 2. Since sodium borohydride or hydrazine hydrate does not have the ability to disperse and stabilize nanoparticles, and cannot be used as an anchoring agent to anchor the nanoparticles on the surface of paper, phosmet detection could not be continued after being reused twice.

[0075] Comparative Example 3

[0076] In this comparative example, the type of hemicellulose was replaced by galactoglucomannan from xylan, and the other parts were the same as in Example 1. Since galactoglucomannan has fewer reducing aldehyde groups and poor water solubility, Au or Ag or Au-Ag nanoparticles cannot be prepared with high efficiency, and the prepared nanoparticles are large in size, poorly dispersed, and difficult to anchor on the paper base surface. The prepared substrate has poor Raman enhancement performance, and the lower limit of detection concentration of methyl parathion is 50 times that of xylan, and methyl parathion cannot be detected after repeated use for 5 times.

[0077] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a rapid detection test paper for organic pollutants based on xylan-assisted surface enhanced Raman scattering, characterized in that: The following steps are involved: (1) xylan and / or modified xylan and gold ions are subjected to a reduction reaction with a solvent as a reaction medium to obtain a xylan / gold nanoparticle mixture, and the xylan / gold nanoparticle mixture is coated on a paper surface to obtain a gold nanoparticle-immobilized paper substrate; (2) immersing the gold nanoparticle-immobilized paper substrate in a solution containing silver ions, and reducing the silver ions by xylan on the gold nanoparticle-immobilized paper substrate and / or other auxiliary means to obtain a gold-silver bimetallic nanoparticle-immobilized test paper; In the gold nanoparticle-immobilized paper substrate obtained in step (1), the ratio of the mass of the gold nanoparticles to the area of ​​the paper is 0.5 to 15 g / m 2 ; The molar ratio of gold in the gold nanoparticle-immobilized paper substrate obtained in step (1) to the molar ratio of silver in step (2) is 1:0.5-10.

2. According to claim 1, a method for preparing a rapid detection test paper for organic pollutants based on xylan-assisted surface enhanced Raman scattering, characterized in that: The mass ratio of the xylan and / or modified xylan to the gold ion in step (1) is 30:1-27; In the solution containing silver ions in step (2), the concentration of the silver ion solution is 0.1 to 10 mg / mL; The solution containing silver ions also contains xylan and / or modified xylan, and the concentration of xylan and / or modified xylan in the system is 0.1-25 mg / mL; The solution containing silver ions also contains iron oxide and / or iron oxyhydroxide, and the concentration of the iron oxide and / or iron oxyhydroxide in the system is 1 to 20 mg / mL; The solution containing silver ions also contains sodium borohydride, sodium cyanoborohydride and / or hydroxylamine hydrochloride, and the concentration of the sodium borohydride, sodium cyanoborohydride and / or hydroxylamine hydrochloride in the system is 1-20 mg / mL.

3. The method for preparing a rapid detection test paper for organic pollutants based on xylan-assisted surface enhanced Raman scattering according to claim 1, characterized in that: The temperature of the reduction reaction in step (1) is 60-100°C and the time is 10-80 minutes; The immersion time in step (2) is 1 to 5 hours; the other auxiliary reduction methods include at least one of the reduction method of adding xylan as a reducing agent, microwave reaction reduction, chemical reducing agent reduction, and photocatalytic reduction; wherein the power of the microwave reaction of xylan as a reducing agent is 300 to 800 W, the microwave reaction time is 30 to 90 minutes, and the microwave reaction temperature is 60 to 90°C.

4. The method for preparing a xylan-assisted surface enhanced Raman scattering organic pollutant rapid detection test paper according to claim 1, characterized in that: The solution containing silver ions in step (2) is a Tollens reagent, which is prepared by mixing a 0.01-2 mol / L AgNO3 solution and a 0.5-5 wt% strong alkali aqueous solution in a volume ratio of 1:1-30, and then adding a 0.5-5 wt% ammonia aqueous solution until the precipitate just disappears; In step (1), the xylan and / or modified xylan is mixed with the gold ion solution in the form of a solution or dispersion. Before mixing, the concentration of the gold ion solution is 0.1 to 15 mg / mL, and the concentration of the xylan and / or modified xylan solution or dispersion is 10 to 100 mg / mL.

5. The method for preparing a xylan-assisted surface enhanced Raman scattering organic pollutant rapid detection test paper according to claim 1, characterized in that: In step (1), the xylan / gold nanoparticle mixture is coated on the surface of paper on one side or both sides, with the number of coatings being 1 to 20 times per side; the coating speed is 50 to 200 mm / s; the thickness of each coating is 0.1 to 20 μm, the time interval between each coating is 5 to 30 minutes, and the coating drying temperature is 50 to 90°C.

6. The method for preparing a xylan-assisted surface enhanced Raman scattering organic pollutant rapid detection test paper according to claim 1, characterized in that: The xylan or modified xylan used in step (1) is a polysaccharide or modified polysaccharide whose main chain is composed of (1→4)-β-D-pyranose xylan groups extracted from wood fiber raw materials; the wood fiber raw material is at least one of wood, bagasse, corn cobs, crop straw, husks, fruit shells, fruit peels and seed coats; the modified xylan is at least one of carboxylated modified xylan, acylated modified xylan, esterified modified xylan, etherified modified xylan and quaternized modified xylan, and the degree of substitution of the modified xylan is 0.05 to 1.05; The type of paper in step (1) is at least one of filter paper, printing paper, wrapping paper, white paper, kraft paper, household paper, and a substrate prepared with synthetic fibers based on paper forming technology.

7. A rapid detection test paper for organic pollutants based on xylan-assisted surface enhanced Raman scattering, obtained by the preparation method according to any one of claims 1 to 6.

8. Application of the xylan-assisted surface enhanced Raman scattering organic pollutant rapid detection test paper according to claim 7 in the field of organic pollutant detection.

9. The use of a xylan-assisted surface enhanced Raman scattering organic pollutant rapid detection test paper in the field of organic pollutant detection according to claim 8, characterized in that: The pollutants were collected using xylan-assisted rapid organic pollutant detection test strips, and then surface-enhanced Raman scattering detection was performed to analyze the types and contents of organic pollutants. The organic pollutant is at least one of thiram, phosmet, thiabendazole and methyl parathion; the collection method is at least one of immersion, wiping after wetting and drip coating.